2015
DOI: 10.1016/j.chaos.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Bertrand duopoly with differentiated products and nonlinear costs: Analysis, comparisons and new evidences

Abstract: a r t i c l e i n f o Article history: Available online xxx a b s t r a c tThis paper studies mathematical properties and dynamics of a duopoly with price competition and horizontal product differentiation by introducing quadratic production costs (decreasing returns to scale), thus extending the model with linear costs (constant returns to scale) of Fanti et al. [11]. The economy is described by a two-dimensional non-invertible discrete time dynamic system. The paper first determines fixed points and other in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In order to show more clearly the effect of chaos control, we only let 1 Figure 9, and Equation (21) is chaotic. Without chaos control, the dynamic properties of the system (21) are shown in Figure 16.…”
Section: Chaos Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to show more clearly the effect of chaos control, we only let 1 Figure 9, and Equation (21) is chaotic. Without chaos control, the dynamic properties of the system (21) are shown in Figure 16.…”
Section: Chaos Controlmentioning
confidence: 99%
“…Some researchers have studied the Bertrand duopoly with differentiated products. The results show that the degree of product differentiation has a great influence on the price and quantity of sale [1][2][3]. In the Bertrand game model, the amount of information that the duopoly has will affect the stability of the system, mainly reflected in the change of the basin of attraction [4].…”
Section: Introductionmentioning
confidence: 99%
“…And they found that the Nash equilibrium point may lose its stability through a flip bifurcation or a Neimark-Sacker bifurcation. In addition, a lot of researchers have discussed the complex dynamical behaviors of nonlinear oligopolies from different aspects, such as differentiated goods [21][22][23][24][25], heterogeneous firms [26][27][28][29][30][31], and delayed decisions [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Kawabata and Takarada [14] probed into the effect of free trade agreements on the welfare in Bertrand and Cournot competition model under differentiated products. Brianzoni et al [15] studied the mathematical properties and dynamics of a Bertrand duopoly with horizontal differentiated products and nonlinear costs, and the new evidence has been offered. Liu and Wang [16] investigated the quality control game that discussed the different risk attitudes affecting quality control game of supply chain especially in logistics service supply chain, instead of considering one member's risk attitude and ignoring the combination of two members' risk attitudes.…”
Section: Introductionmentioning
confidence: 99%